2017
DOI: 10.1039/c7ra00417f
|View full text |Cite
|
Sign up to set email alerts
|

Franck–Condon simulation for unraveling vibronic origin in solvent enhanced absorption and fluorescence spectra of rubrene

Abstract: ) related to ring wagging plus CC stretching and CH bend motions on the backbone are actually interpreted for solvent enhanced absorption (fluorescence) spectra of rubrene in benzene and cyclohexane solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…This begins from the choice of the electronic structure calculation method, but also includes the representation of the potential energy surfaces and their vibrational structures. The latter is often disregarded but plays an essential role in determining the shape and intensity of absorption and emission spectra (Le Guennic et al, 2012 ; Pedone et al, 2012 ; Avila Ferrer et al, 2013 ; Barone et al, 2014 ; Hodecker et al, 2016 ; Liu et al, 2016 ; Padula et al, 2016 ; Hu et al, 2017 ; Fortino et al, 2019 ). With these considerations in mind, an extensive study of the methods available to describe excited-states properties of molecular systems of this size can be highly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…This begins from the choice of the electronic structure calculation method, but also includes the representation of the potential energy surfaces and their vibrational structures. The latter is often disregarded but plays an essential role in determining the shape and intensity of absorption and emission spectra (Le Guennic et al, 2012 ; Pedone et al, 2012 ; Avila Ferrer et al, 2013 ; Barone et al, 2014 ; Hodecker et al, 2016 ; Liu et al, 2016 ; Padula et al, 2016 ; Hu et al, 2017 ; Fortino et al, 2019 ). With these considerations in mind, an extensive study of the methods available to describe excited-states properties of molecular systems of this size can be highly valuable.…”
Section: Introductionmentioning
confidence: 99%
“…From the measured normalized-spectra comparison, it was demonstrated that the both phenomena did not affecting the visible color. 21 In order to investigate the solvent effect showing different ECL intensities based on the two-different solvent systems, reduction-oxidation (redox) behaviors were measured by potentiostatic cyclic voltammetry (CV) in the potential range of À2.4 V to +2.4 V with various scan rates of 0.5, 1.0, 2.0, 3.0, 4.0 and 5.0 V s À1 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…From the measured normalized-spectra comparison, it was demonstrated that the both phenomena did not affecting the visible color. 21 …”
Section: Resultsmentioning
confidence: 99%
“…From these calculations, we can also determine the transition energy ω e , and the transition dipole moment d m for the maximal emission (in the Tamm-Dancoff approximation [38]). Finally, we compute the vibronic spectrum for onephoton emission using the Franck-Condon approach [39], and extract the displacement matrix K in the Duschinsky transformation [40] Q ν = JQ + K (with J matrix representing the normal mode mixing during the transition). The Huang-Rhys factors can be computed according to the relationship S ν = (4π 2 ω ν c/2h)K 2 ν .…”
Section: Electronic and Vibrational Analysis Of Methylene Blue Moleculementioning
confidence: 99%